2003
DOI: 10.4081/ijas.2003.3
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the lipid fraction of foods of animal origin by dietary means: rumen activity and presence of trans fatty acids and CLA in milk and meat

Abstract: The recent literature dealing with the effect of the diet on the quality of milk and meat fat is reviewed. Some aspects of the rumen metabolism of lipids are dealt with: lipolysis, bio-hydrogenation, synthesis of microbial fatty acids and inhibition mechanisms on fermentation. Firstly, the influence of forage is considered. Pasture is the best forage, better if high hill pasture, as compared to hay and silage: short chain fatty acids (SCFA) (shorter than C10) are increased, medium chain fatty acids (MCFA) (C12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Organic yoghurt showed cis-9,trans-11 CLA average value of 6.05 mg/g fat; a large variability was observed in this products class that is probably due to cows feeding which influences the fat composition of milk. The recent literature dealing with the effect of the diet on the quality of milk fat was reviewed by Bauman et al (1999) and Antongiovanni et al (2003). Many dietary factors are known to affect CLA in milk fat; they are grouped into categories relative to the potential mechanism by which they may act.…”
Section: Cla Concentration In Yoghurt and Fermented Milkmentioning
confidence: 99%
“…Organic yoghurt showed cis-9,trans-11 CLA average value of 6.05 mg/g fat; a large variability was observed in this products class that is probably due to cows feeding which influences the fat composition of milk. The recent literature dealing with the effect of the diet on the quality of milk fat was reviewed by Bauman et al (1999) and Antongiovanni et al (2003). Many dietary factors are known to affect CLA in milk fat; they are grouped into categories relative to the potential mechanism by which they may act.…”
Section: Cla Concentration In Yoghurt and Fermented Milkmentioning
confidence: 99%
“…Some studies reported a greater proportion of linolenic acid and its derivatives in the fat of grazing sheep than those fed concentrate diets, consistent with the results of this work (Woods and Fearon, 2009;Oliveira et al, 2013). Although the most studies usually find higher biohydrogenation in forage fed animals than in concentrate fed animals, another authors reports lower biohydrogenation in the rumen when the diet is composed of a higher level of forage (Antongiovanni et al, 2003;Abidi et al, 2009;Buccioni et al, 2009).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The most biologically active isomer is Rumenic Acid (RA), the cis9 trans11 isomer, synthesized in ruminants partly in rumen, by isomerization of LA, and partly in the mammary gland by Δ 9 desaturation of vaccenic acid (VA) (Griinari and Bauman, 1999). Sheep milk is rich in CLA, since it has a higher fat content than that from cows or goats and because sheep feeding regimen is often based on pasture (Antongiovanni et al, 2003;Mele, 2009). The production of sheep cheese plays an important economic role in the Mediterranean area where dairy sheep is present since ancient times.…”
Section: Introductionmentioning
confidence: 99%